Numerical investigation of oleo-pneumatic shock absorber: setup and validation - Sheikh Al-Shabab, Ahmed A.; Vitlaris, Dimitrios; Lin, Zhonglu; Grenko, Bojan; Tsoutsanis, Panagiotis; Antoniadis, Antonis; Skote, Martin (ECCOMAS, 2021)
The simulation of an oleo-pneumatic shock absorber is discussed focusing on the solver validation and high fidelity case setup. The multi-physics nature of the problem is tackled by conducting a range of validation cases in the base areas expected to be of relevance. A dynamic system model of the shock absorber is used to generate physically consistent boundary conditions. In addition, steady RANS simulations provide a preliminary insight into the internal flow development and to assist in the design of higher resolution grids.
Keywords: shock absorber; multi-physics; CFD; OpenFOAM